2022
DOI: 10.32615/ps.2021.054
|View full text |Cite
|
Sign up to set email alerts
|

Differences in susceptibility to photoinhibition do not determinegrowth rate under moderate light in batch or turbidostat - a studywith five green algae

Abstract: Abbreviations: ETR -electron transfer rate; ETR(II) -electron transport rate calculated by taking into account the relative absorption cross-section of PSII; ETRMAX -maximum electron transport rate; Fv/Fm -ratio of variable to maximum fluorescence; Ik -minimum saturating light intensity; OD -optical density; RLC -rapid light curve; α -light-use efficiency; σII(λ) -wavelength-dependent functional cross-section of PSII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We concluded that the less the inoculating cell concentration was, the higher the growth rate was. This observation can explain the anomaly of growth rates measured in turbidostats [37].…”
Section: The Generation Time Is Dependent On Cell Concentrationmentioning
confidence: 52%
“…We concluded that the less the inoculating cell concentration was, the higher the growth rate was. This observation can explain the anomaly of growth rates measured in turbidostats [37].…”
Section: The Generation Time Is Dependent On Cell Concentrationmentioning
confidence: 52%
“…The F v /F m ratio, which makes it possible to verify whether there was damage to the photosynthetic apparatus, is a variable that represents the maximum photochemical efficiency of PSII in a condition in which all reaction centers are open and receive a pulse of light saturating. Under stress conditions, such as the reduction of N availability in the plant, there may be a decline in the values of this trait, which indicates possible damage to the photochemical machinery [46,47]. Therefore, genotypes that present tolerance mechanisms to protect the PSII may show insignificant reductions or even higher values for this measure, even in stressful situations [48][49][50].…”
Section: The Effect Of Nitrogen Deprivation On Photosynthesis Maximum...mentioning
confidence: 99%
“…the rate-limiting steps during the dark-to-light transition of PSII and its dependence on the lipid environment in isolated PSII core complexes from the cyanobacterium Thermosynechococcus vulcanus. The research paper by Mattila et al (2022), submitted by Esa Tyystjärvi, deals with studies on the general question of the growth limitation and the susceptibility to photoinhibition, under batch and turbidostat growth modes in several algae. The paper by Yuan et al (2022), submitted by Ya (David) Guo presents the concept of a flexible, computercontrolled plant growth chamber with a feedback mechanism that can utilize photosynthesis models in practical agriculture.…”
mentioning
confidence: 99%